Targeting the Needs of Self-Determination Theory: An Overview of Mental Health Care Apps - Brownlow, Luke (European Journal of Mental Health, 2022)
Introduction: Smartphone apps are a highly accessible tool to supplement self-treatment for mental health challenges, such as depression, and are underrepresented in research. While many studies have performed content analyses of health apps, few studies have reviewed their adherence to behavior theory. Aims: The objective of this study is to assess mHealth depression apps through the lens of the Self-Determination Theory and identify if app functions target the three basic needs: autonomy, competence, and relatedness. Methods: All depression apps available from iTunes and Google Play that met inclusion criteria were analyzed (N = 194). Apps were reviewed for price options, store availability, download rates, and how functions targeted the three basic needs for intrinsic and sustained health behavior change outlined in the Self-Determination Theory. Results: Findings showed that most of the apps targeted at least one of the basic needs (158/194, 81.4%). However, only a few of these apps targeted all three basic needs to some degree (15/194, 7.7%), and no single app targeted all three basic needs fully. Furthermore, neither store availability, price option nor download rates were accurate predictors that apps targeted the three basic needs. Conclusions: The results suggest that some depression apps targeted autonomy, competence, and relatedness but this was limited to a small number of apps through few functions available in each app. People who want access to more functions targeting the needs would need to download a suite of apps.